Gold nanorods with an ultrathin anti-biofouling siloxane layer for combinatorial anticancer therapy. (13th September 2020) - Kim, Jinjoo; Keum, Hyeongseop; Kim, Hansol; Yu, Byeongjun; Jung, Wonsik; Whang, Changhee; Seo, Changjin; Park, Ji Ho; Jon, Sangyong
Abstract: Despite the wide utility of gold nanorods (GNRs) in biomedical fields, only a few methods for modifying or coating the surface of GNRs suitable for biomedical applications are available. In this study, we report a new facile method that enables formation of an ultra-thin (nanometre-thickness) siloxane layer on GNRs with anti-biofouling properties and ligand functionalisation ability. A triblock random copolymer, poly(TMSMA- r -PEGMA- r -NAS), was used to coat GNRs. An ultrathin polymeric shell was formed surrounding GNRs through acid-catalysed crosslinking of silicates of TMSMA. The polymer-coated GNRs (p-GNRs) exhibited high colloidal stability in biological solutions of high ionic strength and long-term stability superior to that of PEG2k -S-GNRs. The functionalities of NAS were demonstrated using two methods for conjugating targeting ligands and loading doxorubicin via electrostatic interactions. The ligand-specific cancer-targeting ability and combinatorial chemo-photothermal anticancer effects were validated in vitro and in vivo, suggesting their potential utility in various fields.